Oxamate-mediated inhibition of lactate dehydrogenase induces protective autophagy in gastric cancer cells: Involvement of the Akt–mTOR signaling pathway. Issue 1 (1st March 2015) - Zhao, Zhi; Han, Fanghai; Yang, Shibin; Wu, Jianhai; Zhan, Wenhua
Abstract Cancer cells produce a substantial amount of energy through aerobic glycolysis even in the presence of adequate oxygen. Lactate dehydrogenase (LDH), a key regulator of glycolysis, reversibly catalyzes the conversion of pyruvate to lactate. Recently, oxamate, an inhibitor of LDH, has been shown to be a promising anticancer agent. However, the detailed mechanism remains largely unclear. In this study, we demonstrate that oxamate inhibits the viability of human gastric cancer cells in a dose- and time-dependent manner. In addition, treatment with oxamate induces protective autophagy in gastric cancer cells. Moreover, autophagy inhibited by chloroquine or Beclin 1 small interfering RNA (siRNA) enhances oxamate-induced apoptosis and proliferation inhibition. Further study has shown that oxamate treatment significantly augments reactive oxygen species (ROS) production. Furthermore, cells pretreated with N-acetyl cysteine (NAC), a ROS inhibitor, display significantly reduced ROS production and attenuated oxamate-induced autophagy. Finally, functional studies reveal that the Akt–mTOR signaling pathway, a major negative regulator of autophagy, is inhibited by oxamate. Together, our results provide new insights regarding the biological and anti-proliferative activities of oxamate against gastric cancer, and may offer a promising therapeutic strategy for gastric cancer.